Development or reflections of the nonprofit sector in Central and Eastern Europe and Hungary - Kákai László (Sciendo, 2020)
The CEE countries are celebrating the 15th anniversary of joining the European Union. The ‘feast’ is also of note because the EP elections are just in front of us. Instead of weighing up the expected results, we can surmise that the resolution of Central European voters is now weaker in terms of belonging to the European community and their trust in democratic institutions is also considerably lower than it was in the transition era. But what happened? The answer is too complex to be summarised in just one study; the examination of this issue would require a complex analysis of facts from economic transformation to transitions in social and economic subsystems. Of these elements, I wish to introduce the system-level transformation and the current state of civil society.